(untitled) (مجلة إحالات, 2026)
Sheikh Abdelhamid Ben Badis (1889–1940) isconsidered as one of the intellectual and cultural figures celebrated in the modern cultural history of Algeria. His reformist visions have attracted the interest of many scholars who have attempted to frame his statements and explore his intellectual and visionary references. However, modern Algerian criticism studieshave not focused much on his critical efforts, assuming that what the Sheikh has contributed in the field of literary criticism amounted to only some superficial comments on the linguistic and stylistic foundations of texts or their impressionistic effects. This represents a limited perspective on his critical achievement, as his critical propositions are in fact deeper than mere impressionistic taste or linguistic commentary. Through this research paper, we will attempt to highlight his most important critical propositions, while also examining his critical methodthatcombinedboth a moral and an ideological approach, blending theoretical output with practical application on several occasions.